Clinical & etiological profile of acute undifferentiated fever in patients admitted to a teaching hospital in Pondicherry - M. K. Uthaya Sankar; Suhaim Latif Perumbadi; Shenbagaram K.; Hanushraj R. (International Journal of Medical Research and Review, 2018)
Objectives: To identify the infectious aetiology and clinical features of Acute Undifferentiated Fever among patients admitted to a teaching hospital in Pondicherry.Design: Prospective observational study.Subjects: 270 cases comprising all adult patients (≥18 years) admitted to the hospital with fever of less than 14 days duration, temperature ≥38ºC upon admission and non-detection of any specific foci of infection by history, physical examination and routine investigations. Previously diagnosed cases of known fevers, collagen vascular disorders, endocrine disorders, malignancies, immunodeficient states, fever of duration ≥14 days and drug induced fevers were excluded.Methods: All patients were examined and investigated according to study protocol after an informed consent to reach final diagnosis.Results: 38.1% cases were of Scrub Typhus aetiology, 20% cases tested positive for dengue, 14.1% cases came positive for Enteric fever and Malaria was found in 5.6% cases, all of P. vivax parasite. There was 1 case of TB, 1 case of candida infection and 1 case of Klebsiella pneumonia. 1 case tested positive for leptospirosis. Blood pathogens isolated were Pseudomonas and Enterococci with 1 case each. UTI was a frequent diagnosis with 7 cases of E. coli, 1 case of Enterococci and 1 case of Staphylococci. 1 case of HIV was detected.Conclusion: Scrub typhus was the most common aetiology of Acute Undifferentiated Fever followed by Dengue and Enteric fever.